Semantics-driven development for electronic government applications - Crichton, C; Davies, J; Gibbons, J; Harris, S; Shukla, A; Tsui, A (2009)
It has been argued that the challenges in electronic government are purely social: that existing methods and tools are perfectly adequate, and that electronic government projects fail because of people, not technology. While acknowledging that there are organisational and political challenges, this paper argues that there is also a significant, technical challenge, and a corresponding technology gap. It argues also that this challenge may be addressed through a combination of model-driven development and semantic technologies, and reports briefly upon a successful, prototypical application. © 2009 IEEE.